Measuring macro- and micronutrient intake in multi-purpose surveys: Evidence from a survey experiment in Tanzania - Hannah Ameye; Joachim De Weerdt; John Gibson (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2020)
The nutrition transition in developing countries has increased interest in moving the measurement and analysis of nutritional choice beyond calories to a more complete understanding of macro- and micronutrient consumption. To help move the literature on data collection forward we randomly assigned six different survey modules to measure food consumption across Tanzania, three using diaries and three using recall methods. These modules were chosen to reflect the variety of modules currently in use in multipurpose household surveys collecting food consumption expenditures in some detail at national scale. They differ by survey observation period, by length of the food recall list, by type of survey reporter (individual reporting or a single reporter per household) and by frequency of interviewer visits. From these data we calculate the percentage consumed relative to daily recommended intakes of calories, protein, fats, sugars, fiber and 16 micronutrients, taking into account age and gender. We also calculate minimum cost diets in each region, using linear programming, and cost-of-basic needs food poverty lines, the prevalence and depth of food poverty according to these lines, and the cost of targeted transfers designed to eliminate food poverty.
Keywords: 330; Consumption; Household surveys; Nutrition; Poverty